Determinants of Improving Service Quality Based on the Kolcaba Comfort Model in the Emergency Department - Zelyu Fitri; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi; Silvia Nora Anggraini (Indonesian Journal of Global Health Research, 2026)
Kolcaba's Comfort Theory emphasizes holistic nursing care by fulfilling patients' comfort needs in four contexts: physical, psychospiritual, sociocultural, and environmental. The Emergency Department (ED) is a high-pressure healthcare setting that requires not only rapid and accurate clinical interventions but also comfort-based nursing services. This study aimed to analyze the determinants of Kolcaba Comfort Theory–based nursing care in the Emergency Department of PMC Hospital, Pekanbaru. This study employed a quantitative method with a cross-sectional design. A total of 96 respondents were selected using purposive sampling. Data were collected using a questionnaire. The questionnaire was tested for validity and reliability before data collection. All items were declared valid based on the Pearson correlation test, and the instrument was reliable with a Cronbach’s alpha value > 0.70. Analyzed using chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis. The bivariate analysis showed significant associations between age (p=0.027), educational level (p=0.001), effective nurse communication (p=0.001), and service environment (p=0.001) with Kolcaba Comfort Theory–based nursing care. However, multivariate analysis revealed that only educational level (p=0.000; OR=31.889; 95% CI=6.395–159.014) and service environment (p=0.024; OR=0.155; 95% CI=0.031–0.785) remained statistically significant. Educational level was identified as the most dominant determinant. The final model showed a Nagelkerke R Square value of 0.707 and an overall classification accuracy of 90.6%. Conclusion: Kolcaba Comfort Theory–based nursing care in the Emergency Department of PMC Hospital, Pekanbaru is significantly influenced by patients’ educational level and the service environment, which contribute to achieving holistic patient comfort.